The son of man: “Is it constructive theology and history of Jesus for the New Testament writing?” - Halim Wiryadinata (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2020)
Many scholars and lay people try to figure out the reasons why the Lord JesusChrist uses the title of the son of man to designate Himself. He uses the title ofthe son of man throughout the Gospels, but there are some incidents only appear outside of the Gospels. This appearance is impressing to find out the reasons why the term occurrences in the Gospel. However, the term also appears in few passages outside the Gospels. Therefore, using the method of critical analysis through the library research as the qualitative methodology in order to seek the development of the argument from beginning up today and to see how the New Testament scholars clear up the message of Jesus in using that title. Few scholars comment that term has significant for the Christological development of the New Testament due to the messianic proclamation as thesaviour of the world. Furthermore, the idea of representative between man andGod apparently introduces the idea of the high priest in the New Testamentwriting for Jesus’ Christology. This idea will bring the consumption for BiblicalTheology when scholars seek this terminology in the New Testament writing.